Unionization and the evolution of the wage distribution in Sweden: 1968 to 2000 - Albrecht, James W.; Björklund, Anders; Vroman, Suzan B. (Bonn, 2009)
"We examine the evolution of the Swedish wage distribution over the periods 1968-1981 and 1981-2000. The first period was the heyday of the Swedish solidarity wage policy with strongly equalization clauses in the central wage agreements. During the second period, there was more scope for firm-specific factors to affect wages. We find a remarkable compression of wages across the distribution in the first period, but in the second period, wage growth was quite uniform across the distribution. We decompose these changes across the distribution into two components – those due to changes in the distribution of characteristics such as education and experience and those due to changes in the distribution of returns to those characteristics. The wage compression between 1968 and 1981 was driven by changes in the distribution of returns, but between 1981 and 2000, the change in the distribution of returns was neutral with respect to inequality. "